The introduction of the concept of personality of future specialists' socionomics jobs at the university - Chuiko, O. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
The article is showing the concept of personal development of the experts of socionomics jobs during the study at the university.The results of empirical research are devoted to process of learning about structures of personality of students who are studying "psychology" and "social work". The results demonstrate the heterogeneity of the formation of value, motivational and personal sphere in the university. This shows spontaneous and unpredictable nature of personal maturity and a "gap" between the professional and personal development of student's age in which professional component of personal advances.Presented author's concept (educational technology) includes four stages of personal development (motivation, activity, project and management). Each step accompanied by changes in the objectives and results of education; changing the types of professional practices, which included students at every stage (volunteer, research, design, management); redeployment teacher at each stage (facilitator, coach, organizer, partner).The concept allows overcoming the barriers between the demands of the labor market and academic background of the student.
Keywords: personal development; personal maturity subject of professional activity; the level of development of personal maturity subject of professional activity; personal ability